Yurisdiksi Negara vs. Yurisdiksi Ekstrateritorial - Suryokusumo, Sumaryo (UI Scholars Hub, 2005)
Under general principle of law, every State has exclusive jurisdiction within its own territory. The State jurisdiction would cover inter alia jurisdiction over its resident nationals and non-resident nationals, including that of the aliens, the subjects of which are now under consideration of this article. However, such jurisdiction is not an absolute one, rather it is subject to certain limitations imposed by international law. The internatinal instruments such as Vienna Conventions 1961 and 1963 for instance are both governing such limitations by creating extrateritorial jurisdiction, in which Diplomatic and Consular Missions maye exercise it in the receiving State.